TAS‐Indolid und TAS‐Carbazolid: Strukturen von [TAS] + [IndHInd] − und [TAS] + [Carb] − ·½CarbH - Marco Müller; Enno Lork; Rüdiger Mews (Zeitschrift für anorganische und allgemeine Chemie, 2005)
TAS Indolide and TAS Carbazolide: Structures of [TAS] + [IndHInd] − and [TAS] + [Carb] − ·½CarbH From the reaction of TAS‐fluoride [(Me 2 N) 3 S] + [Me 3 SiF 2 ] − with trimethylsilyl‐indole and trimethylsilyl‐carbazole TAS‐indolide and TAS‐carbazolide are formed. During crystallisation partially protonation to indole and carbazole occurs, resulting in the formation of [TAS] + [IndHInd] − ( 3a ) and [TAS] + [Carb] − ·½CarbH ( 5a ) according to X‐ray analysis.